The impact of strategic and electronic purchasing initiatives on manufacturing performance - Engin, Aykut (My University, 2006)
İş ortamlarında son yıllarda yaşanan değişimler firmaların kendi içlerinde yeni rekabetçi avantajı aramayı düşünmelerine neden olmuştur. Bu tez, stratejik kaynak temini, e-tedarik gibi stratejik ve elektronik satınalma uygulamalarının esneklik ve tedarik zinciri performansı bağlamında üretim performansına olan etkilerini araştırmıştır. Anket çalışması önceki çalışmalara göre geliştirilmiştir. Buna göre, Türkiye’de Sanayide faaliyet gösteren 106 işletme dağıtılan ankete cevap vermiştir. Verinin analiz edilmesi önceki çalışmaların çıktılarını desteklemiştir. Bu çalışma Satınalma ve Tedarik Zinciri Yönetimi araştırmasına çok sayıda teorik katkıda bulunmuştur. Stratejik kaynak temini ve e-tedarik uygulamalarının alt boyutlarının tedarik zinciri performansına güçlü ve direkt etkide bulunduğunu gösteren yönetimsel bulgular ortaya çıkmıştır. E-tedarik’in şimdilik adaptasyonunun başlangıç aşamalarında olmasına rağmen müşteri memnuniyeti ve mali anlamda tedarik zinciri performansına belirgin etkisi saptanmıştır.

Changes in the business environments over the last years have resulted in new ways of thinking within firms, in their search for competitive advantage. This has resulted that purchasing has been elevated to a strategic level and has become established as an important area of study. This dissertation has investigated the impact of strategic and electronic purchasing initiatives like strategic sourcing, e-procurement on manufacturing performance by means of flexibility and supply chain performance. The survey instrument has been developed based on the past studies. Accordingly, 106 manufacturing firms operating in Turkey have answered the distributed questionnaires. The analysis of data has supported to the findings of previous studies. This study has provided several theoretical contributions to Purchasing and Supply Chain Management research. Several useful managerial implications have also emerged, indicating that sub-dimensions of strategic sourcing and e-procurement practices had strong and direct effect on supply chain performance. As for e-procurement, despite the fact that the level of adoption was currently in early stages, it has been perceived to have a significant impact on customer satisfaction & financial related supply chain performance.
Keywords: Esneklik; Stratejik Planlama; Tedarik Zinciri Yönetimi